EFFICIENCY OF WORKING CAPITAL ON COMPANY PROFITABILITY IN GENERATING ROA (CASE STUDIES IN CV. TOOLS BOX IN SURABAYA) - J.E. Sutanto; Yanuar Pribadi (Universitas Hayam Wuruk Perbanas, 2012)
The purpose of this study is to investigate the influence of the working capital efficiency ratiotoward profitability. The working capital efficiency ratios used in this study are a currentratio, a receivable turnover, and a net working capital turnover. On the other hand, corporateprofitability used in this study is measured by return on assets (ROA). This research isconducted as the case study in a company, namely CV. Tools Box. The data are the monthlyfinancial reports from January 2008 until December 2009. For data analysis, the researcherused a multiple regression analysis, t-test, F-test, coefficient of determination, partial correlation,and classical assumptions. The result of this study indicates that only partially networking capital turnover has a significant effect on ROA. In Addition, the current ratio, receivableturnover, and net working capital turnover simultaneously has a significant effect onROA.